Tracing the History of Islamic Economic Thought in Southeast Asia: From Sultanate Rule to the Modern Era - Kukuh Trisnafi; Ning Wijayanti; M. Arif Faizin (Walidem Institute and Publishing, 2025)
Objective: This study aims to analyze the historical traces of Islamic economic civilization in Southeast Asia, with a focus on the transformation of the economic system in Indonesia, Malaysia, and Brunei Darussalam, from the era of the Sultanate to the development of modern Sharia banks. Theoretical framework: This study uses Islamic economic concepts such as the prohibition of usury, distributive justice (adl), and social welfare (falah), as well as the theory of institutional transformation and economic history, to analyze changes in the Islamic economic system. Literature review: The literature review includes a study of Islamic economics, the history of Islamic civilization in Southeast Asia, and the development of Islamic banks. The focus is on how Islamic economic principles are applied in the modern banking system and the role of the Sharia Supervisory Board in maintaining economic morality. Method: This study uses a qualitative method with a literature study, collecting data from various historical and contemporary sources to understand the transformation of the Islamic economic system in the Southeast Asian region. Results: The results show the continuity of Islamic economic values, such as the prohibition of usury and distributive justice, from the Sultanate to the implementation of Sharia Bank products based on profit sharing (mudharabah/musharakah). Sharia banks also play a role in the management of social funds and the supervision of economic morality. Implications: These findings can strengthen a more equitable and ethical economic system in Southeast Asia by strengthening Islamic economic principles in the context of contemporary economics and the role of Islamic banks. Novelty: This study combines the study of the history of Islamic economics with the development of Islamic banks, providing new insights into the relevance of Islamic economic values in the framework of modern economics, as well as recommending cross-disciplinary research to understand the evolution of this system.